Problems Related to the Changes in the Palestinian Criminal Procedures Law - Muhammad Subhi Muhammad Khateeb (My University, 2010)
This study aimed to address the issue of the problems in the execution of the Palestinian Penal Procedures Law in light of the absence of books of fiqh in the legal library which address this issue. The study also discussed the legal nature of the problems of the execution of penal provisions in general in the first chapter. It addressed those problems in three sections terms of their definition, types and the way they are different from other concepts in addition to discussing the reasons behind those problems. After that, the study began to explain the idea of the problematic execution and the legal system that governs those problems as well as the type of court that specializes in such issues. The study further discussed the dispute over what type of courts that should address and deal with this matter. Fiqh has been divided into four trends with respect to the determination of the type of court that would be responsible for settling the case of problematic execution of penal procedures. Some argued that the Attorney General is the responsible body for the execution of penal provisions, thus, it is the one responsible for the resolution of conflicts that emerge during the execution of a penal provision. Others argued that the civil court in which execution occurs is the responsible court which takes decisions regarding problematic execution. Another party said that the court of misdemeanors is the one responsible for cases related to problems in the execution of penal provisions. The fourth and final group argued that the court which issued the judgment in the first place is the one that must be responsible for dealing with the case of problematic execution of penal provisions since it is the only one which have a full knowledge about the case and has a complete understanding of the different aspects of the problematic execution of penal provisions. The Palestinian Penal Legislature has authorized the court which issued the order to follow up with the case of the problematic execution of penal provisions. The case is forwarded to the court that issued the ordered according to article 420 of the Palestinian Penal Procedures Law No. (3) 2001. After that, the researcher examined the legal system of the problematic execution case in the second chapter. He addressed the specialty in considering the problematic execution, the conditions that are required to accept the case, its procedures and finally the adjudication of the case.

تهدف هذه الدراسة للوقوف على موضوع إشكالات التنفيذ في قانون الإجراءات الجزائية الفلسطيني، خاصة لخلو المكتبة القانونية من الكتب الفقهية التي تناولت هذا الموضوع الهام، ودراسة موقف الفقه والقضاء من موضوع الإشكالات التي تعترض إجراءات تنفيذ الأحكام الجزائية. تناول الباحث الطبيعة القانونية لإشكالات تنفيذ الأحكام الجزائية بشكل عام في الفصل الأول، وذلك في ثلاثة مباحث بحيث تناول ماهية إشكالات التنفيذ والتعريف بها وبأنواعها في المبحث الأول, وتمييزها عن المفاهيم الشبيهة الأخرى في المبحث الثاني، ومن ثم تم التطرق إلى أسباب الإشكال التنفيذي في المبحث الثالث. وبعدها تم الانتقال إلى دراسة معمقة لدعوى الإشكال في التنفيذ، والنظام القانوني لإشكالات التنفيذ، والمحكمة المختصة بالنظر والبت في الاستشكال التنفيذي والفصل فيه، فقد تم التعرض بالدراسة إلى الخلاف والجدل الفقهي حول تحديد المحكمة المختصة بنظر الإشكال التنفيذي، حيث تعددت الآراء الفقهية في تحديد المحكمة المختصة وانقسم الفقه إلى أربعة اتجاهات بتحديد المحكمة التي تختص بالفصل في دعوى الإشكال التنفيذي: فمنهم من ذهب إلى أن النيابة العامة هي صاحبة الاختصاص الأصيل في تنفيذ الأحكام الجزائية، وبالتالي فهي المختصة بحل النزاعات التي تظهر أثناء تنفيذ الحكم الجزائي، ومنهم من رأى أن المحكمة المدنية التي يجري بدائرتها التنفيذ هي المحكمة المختصة بالبت في الإشكال التنفيذي والفصل فيه كونها صاحبة الاختصاص العام، وقد اتجه رأي آخر إلى أن محكمة الجنح المستأنفة هي المحكمة المختصة بإشكالات التنفيذ، أما الاتجاه الرابع والأخير فقد ذهب إلى أن الاختصاص ينعقد للمحكمة التي أصدرت الحكم كونها أعرف وأكثر قدرة من غيرها على فهم كافة جوانب الدعوى الجزائية المستشكل في إجراءات تنفيذ الحكم الصادر بها. وقد منح المشرع الجزائي الفلسطيني المحكمة التي أصدرت الحكم الاختصاص بنظر دعوى الإشكال التنفيذي والفصل فيه، بحيث يرفع الإشكال التنفيذي إلى المحكمة التي أصدرت الحكم وذلك وفق نص المادة (420) من قانون الإجراءات الجزائية الفلسطيني رقم(3) لسنة 2001م، ووفقاً للقواعد العامة، فإن الحكم الصادر في دعوى الإشكال التنفيذي يكون قابلاً للطعن بكافة طرق الطعن العادية وغير العادية. كما تناول الباحث النظام القانوني لدعوى الإشكال التنفيذي في المادة الجزائية في الفصل الثاني وذلك في ثلاثة مباحث، حيث تناول الاختصاص بنظر الإشكال التنفيذي في المبحث الأول، وشروط الإشكال التنفيذي وإجراءات النظر فيه في المبحث الثاني، والفصل في دعوى الإشكال التنفيذي في المبحث الثالث.
إشكالات تنفيذ الأحكام الجزائية في قانون الإجراءات الجزائية الفلسطيني